Towards cultural materialism in the medical humanities: the case of blood rejuvenation. Issue 1 (11th May 2017) - Oakley, Catherine
Abstract : This paper argues for an approach within the medical humanities that draws on the theoretical legacy of cultural materialism as a framework for reading cultural practices and their relationship to the social and economic order. It revisits the origins and development of cultural materialism in cultural studies and literary studies between the 1970s and 1990s and considers how, with adaptation, this methodology might facilitate ideological criticism focused on material formations of health, disease and the human body. I outline three key characteristics of a medicocultural materialist approach along these lines: (a) interdisciplinary work on a broad range of medical and cultural sources, including those drawn from 'popular' forms of culture; (b) the combination of historicist analysis with scrutiny of present-day contexts; (c) analyses that engage with political economy perspectives and/or the work of medical sociology in this area. The subsequent sections of the paper employ a medicocultural materialist approach to examine conjectural understandings of, and empirical investigations into, the capacity of transfused human blood to rejuvenate the ageing body. I trace textual faultlines that expose the structures of power which inform the movement of blood between bodies in 'medical gothic' fictions from the 19th-century fin de siècle, including Mary Elizabeth Braddon's 'Good Lady Ducayne' (1896) and Bram Stoker's Dracula (1897). I conclude with a critique of biomedical innovations in blood rejuvenation in the era of medical neoliberalism, before considering the potential applications of medicocultural materialism to other topics within the field of the medical humanities.